Strategies for Cities in Global Competition: An Essay on Spatial Economics and Management Science. - Albach, Horst (Springer, 2018)
The paper starts with a short history of the economics of cities: one city, location of many cities, competition of cities in a single currency region, global competition of cities. The chapter second section deals with the strategies of cities that compete with each other for growth, attractiveness and welfare of the citizens. The city of Bonn is used as an example. The limitations of competition strategies are described using the example of Trier. Legal structures of Chicago and Tokyo are analysed for comparison.
Keywords: Stadtökonomie; Wettbewerb; Wirtschaftsentwicklung; Stadtentwicklung; Globalisierung; Raumökonomie; Fallbeispiel; Städtevergleich